Timing of device reimplantation and reinfection rates following cardiac implantable electronic device infection: a systematic review and meta-analysis - Derek Chew; Ranjani Somayaji; John Conly; Derek Exner; Elissa Rennert-May (BMJ Open)
Objectives Initial management of cardiac implantable electronic device (CIED) infection requires removal of the infected CIED system and treatment with systemic antibiotics. However, the optimal timing to device reimplantation is unknown. The aim of this study was to quantify the incidence of reinfection after initial management of CIED infection, and to assess the effect of timing to reimplantation on reinfection rates.Design Systematic review and meta-analysis.Interventions A systematic review and meta-analysis was performed of studies published up to February 2018. Inclusion criteria were: (a) documented CIED infection, (b) studies that reported the timing to device reimplantation and (c) studies that reported the proportion of participants with device reinfection. A meta-analysis of proportions using a random effects model was performed to estimate the pooled device reinfection rate.Primary and secondary outcome measures The primary outcome measure was the rate of CIED reinfection. The secondary outcome was all-cause mortality.Results Of the 280 screened studies, 8 met inclusion criteria with an average of 96 participants per study (range 15–220 participants). The pooled incidence rate of device reinfection was 0.45% (95% CI, 0.02% to 1.23%) per person year. A longer time to device reimplantation >72 hours was associated with a trend towards higher rates of reinfection (unadjusted incident rate ratio 4.8; 95% CI 0.9 to 24.3, p=0.06); however, the meta-regression analysis was unable to adjust for important clinical covariates. There did not appear to be a difference in reinfection rates when time to reimplantation was stratified at 1 week. Heterogeneity was moderate (I2=61%).Conclusions The incident rate of reinfection following initial management of CIED infection is not insignificant. Time to reimplantation may affect subsequent rates of device reinfection. Our findings are considered exploratory and significant heterogeneity limits interpretation.PROSERO registration number CRD4201810960.